TREATMENT OF ARTERIAL HYPERTENSION IN YOUNG MALES WITH CLINICAL SIGNS OF AUTONOMIC DYSFUNCTION - Bilovol, O.M.; Kniazkova, I.I.; Bogun, M.V.; Lutsenko, R.V. (World of Medicine and Biology, 2020)
The aim of the study was to improve the effectiveness of the treatment of arterial hypertension (AH) in young patients with clinical signs of autonomic dysfunction. We examined 65 male patients with AH (mean age 35.6 ± 4.3 years) and clinical signs of autonomic dysfunction. Basic therapy was administered to 30 of them (group 1), and ethylmethylhydroxypyridine succinate (EMS) was additionally administered to 35 patients (group 2) for 4 weeks. After treatment, BP correction to target values was achieved in 76.7% of the patients in group 1 and in 88.6% in group 2. On the background of therapy with EMS, a more pronounced increase in total HRV, decreased activity of the sympathetic division of the autonomic nervous system and restoration of the vegetative balance according to the temporal HRV indicators, as well as the significant positive changes in state and trait anxiety were observed. Thus, the inclusion of EMS in the complex treatment of young males with AH and clinical signs of autonomic dysfunction has a positive effect on clinical symptoms, contributes to the restoration of the autonomic balance and correction of psycho-emotional state.
Keywords: arterial hypertension in young; autonomic dysfunction; heart rate variability; anxiety; ethylmethylhydroxypyridine succinate